Renewable energy scenarios: Exploring technology, acceptance and climate – Options at the community-scale. (September 2016) - Gormally, A.M.; Whyatt, J.D.; Timmis, R.J.; Pooley, C.G.
Abstract: Community-based renewable energy could play a key role in the transition to a low carbon society. This paper argues that given the right environmental and societal conditions, communities in the UK could source a high percentage of their electricity supply from a mixture of localised renewable electricity technologies. Here we use exploratory scenarios to assess demand and renewable electricity supply-side options at the community-scale for a location in Cumbria, UK. Three scenarios are presented, using narratives of how local demand and renewable electricity supply could be constructed under either existing or modified environmental and societal conditions. The three scenarios explored were 'Current State of Play', 'Low Carbon Adjusted Society' and 'Reluctant Scenario'. Highlights: The paper explores societal and environmental conditions for local renewable energy. Exploratory scenarios assess demand and renewable options at local scales. Scenarios use narratives of how demand/renewable supply could be constructed. Narratives include existing or modified environmental and societal conditions.